Standardization of Indonesian anti-unemployment laws in accordance with ILO Conventions - Beny Saputra; Olivér Bene (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The Covid-19 epidemic precipitated a substantial recession ranging from 4.4% to 5.2%. The labor market is one of the most impacted industries, as seen by the high rate of layoffs. The government has created a job loss insurance system as part of its broader protection against unemployment program to counteract this eventuality. This study examines the standardization of Jaminan Kehilangan Pekerjaan (Job Insurance Scheme) in Indonesia in accordance with the ILO Convention No. 168 and its goals. Comparative law is the method employed in this study. In analyzing legal materials, this study use qualitative descriptive analysis in conjunction with ILO convention's main factor and aim. This analysis determined that the JKP or Job loss insurance plan in Indonesia meets five main ILO Convention principles and goals.